Dietary supplementation with 25-hydroxyvitamin D3 regulates productive performance, lipid metabolism and gut microbiota in aged laying ducks - Yongyan Jin; Huanting Xia; Wei Chen; Xuebing Huang; Kaichao Li; Shuang Wang; Weiguan Xia; Shenglin Wang; Chang Zhang; Yanan Zhang; Chuntian Zheng (Animal Nutrition)
The aim of this study was to investigate the effect of dietary supplementation with 25-hydroxyvitamin D3 (25(OH)D3) on productive performance, lipid metabolism and gut microbiota in aged laying ducks. A total of 432 healthy Longyan ducks at 60-week of age were randomly allotted to 6 groups, each with 6 replicates of 12 ducks. Ducks were given a basal diet (without added 25(OH)D3) or that diet supplemented with 800, 1600, 2400, 3200, or 4000 IU/kg 25(OH)D3 for a total of 16 wk. Dietary supplementation with 25(OH)D3 improved egg production, egg mass and average daily feed intake, and decreased the feed conversion ratio (FCR) of ducks during the whole trial period (linear, quadratic; P < 0.05). Supplementation with 25(OH)D3 decreased very low-density lipoprotein (VLDL) content in yolk (P = 0.008), decreased high-density lipoprotein and low-density lipoprotein (LDL) content in plasma (P = 0.002). Hepatic index, VLDL, LDL, triglyceride and total cholesterol content in liver, nonalcoholic fatty liver activity score of liver and alanine aminotransferase activity in plasma were decreased with supplementation of 25(OH)D3 (linear or quadratic; P < 0.05). The decreased hepatic apolipoprotein B 100 and lipoprotein lipase expression, and increased hepatic peroxisome proliferator-activated receptor-α and sterol regulatory element binding protein-1 expression resulted from 25(OH)D3 supplementation (linear, quadratic; P < 0.05). Moreover, 25(OH)D3 supplementation increased the villus/crypt ratio (linear, quadratic; P < 0.05) and expression of zonula occludens protein 1 and nuclear factor-κ-gene binding in duodenum (P < 0.05). The supplementation of 25(OH)D3 reduced the abundance of Wittenberg polluted soil-2 bacteria, Synergistota, Bacteroidales, Colidextribacter, Eggerthellaceae, Oscillospira, Oscillibacter, UCG-009, Barnesiellaceae and Lachnospiraceae_UCG-010 in cecal contents (P < 0.05). Dietary requirements for 25(OH)D3 for ducks (60 to 76 wk), were estimated to be 3377 IU/kg for egg production, 3434 IU/kg for egg mass, and 3256 IU/kg for FCR. In summary, dietary 25(OH)D3 supplementation improved productive performance and influenced liver and plasma lipid homeostasis in aged laying ducks, which may be associated with the reduction of bacteria involved in carbohydrate metabolism in the cecum. Supplementing the basal diet with 3250 to 3450 IU/kg 25(OH)D3 is recommended for aged laying ducks (60 to 76 wk).